2010
DOI: 10.5194/bg-7-3259-2010
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification in sediments as a major nitrogen sink in the Baltic Sea: an extrapolation using sediment characteristics

Abstract: Abstract.Rates of denitrification in sediments were measured with the isotope pairing technique at different sites in the southern and central Baltic Sea. The rates varied between 0.5 µmol N m −2 h −1 in sands and 28.7 µmol N m −2 h −1 in muddy sediments and showed a good correlation to the organic carbon contents of the surface sediments. N-removal rates via sedimentary denitrification were estimated for the entire Baltic Sea calculating sediment specific denitrification rates and interpolating them to the wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 60 publications
7
52
3
Order By: Relevance
“…The denitrification rates reported in the present study are similar to those measured in the northern part of the Baltic Sea, the Gulf of Bothnia, but 50 % lower than those found in the southern Bothnian Sea (Stockenberg and Johnstone 1997). Our rates are at least twice as high as rates previously measured in sediment from the open Baltic Proper (Tuominen et al 1998;Deutsch et al 2010), generally comparable to those measured in the Gulf of Finland (Hietanen and Kuparinen 2008;Jäntti et al 2011), but 1.5 to twofold lower than those in muddy sediments of the southern Baltic Sea (Deutsch et al 2010). Compared to measurements in other coastal settings worldwide, our rates and those reported in previous studies from the Baltic are generally low (Seitzinger 1988;Steingruber et al 2001).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The denitrification rates reported in the present study are similar to those measured in the northern part of the Baltic Sea, the Gulf of Bothnia, but 50 % lower than those found in the southern Bothnian Sea (Stockenberg and Johnstone 1997). Our rates are at least twice as high as rates previously measured in sediment from the open Baltic Proper (Tuominen et al 1998;Deutsch et al 2010), generally comparable to those measured in the Gulf of Finland (Hietanen and Kuparinen 2008;Jäntti et al 2011), but 1.5 to twofold lower than those in muddy sediments of the southern Baltic Sea (Deutsch et al 2010). Compared to measurements in other coastal settings worldwide, our rates and those reported in previous studies from the Baltic are generally low (Seitzinger 1988;Steingruber et al 2001).…”
Section: Discussionsupporting
confidence: 76%
“…The spreading of hypoxia and anoxia in the bottom waters since the 1960s (Elmgren 2001;Conley et al 2009) is generally thought to be responsible for significant N loss due to enhanced denitrification in the water column (Rönner 1985;Vahtera et al 2007). While an N deficit in the Baltic has been identified based on budget calculations ), coupled physical biogeochemical models (Meier et al 2012), and gas inventories (Löffler et al 2011), there have been few direct rate measurements in sediments and the water column (Deutsch et al 2010;Jäntti et al 2011;Hietanen et al 2012;Dalsgaard et al 2013). The regional and spatial coverage of benthic flux data for the Baltic is low and most of the existing studies have not investigated the key regulators of benthic N cycling such as temperature, oxygen availability and demand, presence/absence of macrofauna, sedimentary organic matter content, or variable nutrient loading from human activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with denitrification at the pelagic redoxcline calculated from the rate measurements of Brettar and Rheinheimer (1991), this implies a total denitrification of 397 kt N year −1 for the Baltic Proper. For the remaining regions where no pelagic redoxcline exists, Deutsch et al (2010) reported a sediment denitrification of 235 kt N year −1 . Hence, the total denitrification in the Baltic Sea (823 kt N year −1 ) agrees with the upper limit given by Voss et al (2005).…”
Section: Nitrogen Transformationsmentioning
confidence: 99%
“…18.2). Deutsch et al (2010) investigated denitrification in sediments with different physical and chemical properties. The results were extrapolated to the entire Baltic Sea by the use of maps describing sediment characteristics for the entire Baltic Sea.…”
Section: Nitrogen Transformationsmentioning
confidence: 99%